Succession dynamics of microbial communities responding to the exogenous microalgae ZM-5 and analysis of the environmental sustainability of a constructed wetland system. (March 2023) - Zhao, Xinyue; Meng, Xiangwei; Dang, Bin; Zhang, Tuoshi; Shi, Wen; Hou, Ning; Yan, Qingsheng; Li, Chunyan
Graphical abstract: Highlights: Microalgae coupled with CWs for wastewater treatment was proven to be feasible. Nitrogen removal in the CWs was improved by about 20% with the addition of microalgae. There exist interactions between denitrifying bacteria and the microalgae ZM-5. Microalgae could affect C, N, and P functional gene expression by HT-qPCR chip analysis. The use of ultrasonic extraction for lipid extraction had the best environmental effect. Abstract: Constructed wetlands (CWs) are economical and effective swine tailwater treatment systems. However, nitrogen removal in CWs is limited by the lack of carbon source for denitrification. In this study, we studied the feasibility of dosing the microalgae ZM-5 to improve the nitrogen removal ability in CWs. Compared to the control CW, a 20 % higher removal capacity of COD and TN was observed for the coupled system (EG). The microalgae ZM-5 could interact with denitrifying bacteria to compensate for the deficiency of denitrifying stage in CWs. HT-qPCR chip analysis also provided evidence that denitrification genes significantly increased (p < 0.05). According to the life cycle assessment (LCA), ultrasonic extraction had the best environmental sustainability among four lipid extraction processes. As an improvement strategy, clean energy could be utilized to optimize the electricity source to reduce environmental load (45 %–60 %). These findings offer new insights into the feasibility of EG for environmentally sustainable wastewater treatment.